(untitled) (Journal of Ideas in Health, 2021)
Background: The COVID-19 pandemic has profoundly impacted the health of individuals physically, mentally, and socially. This study aims to gain a deeper understanding of this impact across the pandemic from a biopsychosocial stance. Methods: A survey created by the research team was employed between November 2020 and February 2021 across social media, relevant organizations, and networks. The survey incorporated 5-time points across the different stages of the pandemic, covering biological, psychological, and social. There were 5 items for each survey (Very Positive affect to Very Negative affect), and analysis was undertaken using SPSS version 16. Descriptive statistics and non-parametric Friedman and Wilcoxon Tests, as well as correlations between the three domains, were implemented. Results: This study included 164 participants (77.0% female and 35.0% male) across 24 out of 38 counties in the UK. The impact of COVID-19 on biological domain was significant across the five data points χ2(4) = 63.99, p < 0.001, psychological χ2(4) = 118.939, p <0.001 and socially χ2(4) = 186.43, p <0.001. Between the 5 data points, 4 out of 5 had a negative impact, however between the first stage of lockdown and the easing of restrictions, findings for biological (Z=-2.35, p <0.05), psychological (Z=-6.61, p < 0.001), and socially (Z = -8.61, p <0.001) were positive. Negative correlations between the three domains across the pandemic are apparent, but in later stages, the biological domain had a positive correlation r = 0.52, p < 0.001. Conclusion: The data shows a negative impact from the self-reported perception of wellbeing from a biopsychosocial stance over time, as well as perceiving the three domains to interact negatively. To address these biopsychosocial issues, the research implies a place-based integrated recovery effort is needed, addressing biological, psychological, and social issues simultaneously. Further research should investigate biopsychosocial health among a more generalizable population.